Analisis Tapera dalam Perspektif Ekonomi Islam: Keabsahan Konsep dan Tantangan Gharar - Amelia, Nur; Sukmaya, Dwinugrah Yogas; Rahmawati, Destiyana; Hidayat, M. Khoiruddin; Cahyani, Nisa Kurnia; Waluyo, Waluyo (Journal of Economics, Bussiness and Management Issues, 2025)
The Public Housing Savings (Tapera) is an Indonesian government program aimed at assisting low-income communities in obtaining decent housing through a mandatory savings scheme. This study aims to examine the validity of the Tapera concept from an Islamic economic perspective and analyze the potential presence of gharar in its mechanism. A qualitative descriptive research method was employed, utilizing a literature review approach that analyzed various sources, including scientific journals, legislation, and official government statements. The findings indicate that Tapera may involve elements of gharar due to uncertainties in fund management, ownership certainty, and the timeframe for benefit disbursement. While the program's objectives align with the Islamic economic principle of social welfare, its implementation requires greater transparency and legal certainty to comply with Sharia principles. In conclusion, minimizing gharar in Tapera necessitates enhanced transparency in fund management, investment mechanisms based on halal instruments, and assurance of fair and non-exploitative benefits for participants, ensuring its alignment with Islamic economic principles.